Trend of infant mortality, and of its components, in Espírito Santo State/Brazil, from 2006 to 2016 (Brazilian Journal of Health Research, 2020)
Introduction: Infant mortality is an undesirable public health event, mostly because it is avoidable and, therefore, reflects the living conditions of society. The current study has analyzed the temporal trend of infant mortality, and of its components, in Espírito Santo State and in health regions. Methods: Ecological study about infant mortality in Espírito Santo State and in health regions, based on data deriving from the Mortality Information System (SIM), from 2006 to 2016. Mortality coefficients (infant, neonatal, early neonatal, late neonatal, post-neonatal and perinatal) were calculated by dividing the number of children’s deaths per year (based on their place of residence) by the number of children born in the same place and year. Linear regression was used to evaluate the temporal trend. Results: Infant mortality has shown significant decrease in all health regions, the highest reduction rates were recorded for the Northern and Southern regions, whereas the lowest rate was recorded for the Metropolitan Region. However, mortality between the 7th and 27th day of life has increased in the Northern and Central health regions. Infant mortality recorded greatest reduction, and it was followed by perinatal, neonatal, early neonatal, post-neonatal and late neonatal mortality. Conclusion: There was reduced infant mortality in ES and in health regions from 2006 to 2016 perinatal and early neonatal components were the ones recording the highest reduction rates. Late neonatal mortality has increased in the Northern and Central regions; this outcome has emphasized the need of improving public policies to enable rigorous and effective follow-up of children in their first month of life.
Keywords: Infant mortality; Child health; Health services indicators